A Novel Mutation in the CLDN16 Gene in a Palestinian Family with Familial Hypomagnesemia with Hypercalciuria and Nephrocalcinosis - Abu-Libdeh, Abdulsalam; Abu-Libdeh, Bassam; Abdulhag, Ulla Najwa (Journal of Child Science, 2017)
Familial hypomagnesemia with hypercalciuria and nephrocalcinosis (FHHNC) is a rare autosomal recessive renal disorder characterized by excessive renal magnesium and calcium loss, bilateral nephrocalcinosis, and progressive renal failure, due to impaired tubular reabsorption in the thick ascending loop of Henle. FHHNC is caused by loss of function mutations in the claudin-16 gene (CLDN16) and claudin-19 gene (CLDN19). A 2-month-old male infant presented with convulsions during hypomagnesemia, hypocalcemia, and hypophosphatemia, biochemical findings were consistent with FHHNC. There is a positive family history of the death of a 12 years old sibling due to renal failure. Gene sequencing of the CLDN16 revealed a novel missense mutation with the replacement of T by C in codon 120 located in exon 2, predicting cysteine to arginine substitution p.Cys120Arg. This is the first description of this missense mutation and the first confirmation of FHHNC by molecular testing in a Palestinian family which enables genetic counseling and future prenatal diagnosis.
Keywords: CLDN16; CLDN19; familial hypomagnesemia with hypercalciuria and nephrocalcinosis